2022
DOI: 10.1371/journal.pone.0264899
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable customer retention through social media marketing activities using hybrid SEM-neural network approach

Abstract: Social media has changed the marketing phenomenon, as firms use social media to inform, impress, and retain the existing consumers. Social media marketing empowers business firms to generate perceived brand equity activities and build the notion among consumers to continue using the firms’ products and services. The current exploratory study aimed to examine the effects of social media marketing activities on brand equity (brand awareness and brand image) and repurchase intention of high-tech products among Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 89 publications
1
13
0
7
Order By: Relevance
“…Similarly, previous research reported positive relationships between SMMAs and online purchase intention toward luxury brands in Korea (Kim and Ko, 2010), the Indian fashion luxury industry (Gautam and Sharma, 2017) and social media user intentions in Pakistan (Jamil et al, 2022). The third component of the S-O-R theory is consumer response (i.e., purchase/repurchase intention) (Zhu et al, 2020b;Yang et al, 2022). The consumer responses serve as the basis for the current investigation on online repurchase intention, also known as consumer online repurchase intention.…”
Section: H3 Smmas Positively Affects Satisfactionmentioning
confidence: 86%
See 4 more Smart Citations
“…Similarly, previous research reported positive relationships between SMMAs and online purchase intention toward luxury brands in Korea (Kim and Ko, 2010), the Indian fashion luxury industry (Gautam and Sharma, 2017) and social media user intentions in Pakistan (Jamil et al, 2022). The third component of the S-O-R theory is consumer response (i.e., purchase/repurchase intention) (Zhu et al, 2020b;Yang et al, 2022). The consumer responses serve as the basis for the current investigation on online repurchase intention, also known as consumer online repurchase intention.…”
Section: H3 Smmas Positively Affects Satisfactionmentioning
confidence: 86%
“…Prior studies primarily focused on SMMAs examined various concepts in diverse consumer environments. For example, the impact of SMMAs was examined on brand equity in India and Egypt (Yadav and Rahman, 2017;Ebrahim, 2020), value and brand consciousness in Malaysia (Ismail, 2017), customer equity drivers in India (Yadav and Rahman, 2018), consumer brand engagement in Hong Kong (Cheung et al, 2020), consumer brand-related activities (consuming, contributing, and creating) in China (Cheung et al, 2021) and brand image and brand awareness in China (Yang et al, 2022), and consumers' engagement intention and engagement behavior in Pakistan (Shang et al, 2022). Previous research has acknowledged the importance of SMMAs and relationship quality (commitment, trust, and satisfaction) in e-commerce (Yadav and Rahman, 2018).…”
Section: Social Media Marketing Activities and Relationship Quality (...mentioning
confidence: 99%
See 3 more Smart Citations